Relaxation ferroelectric / antiferroelectric superlattice energy storage film and preparation method and application thereof

By using a relaxed ferroelectric/antiferroelectric superlattice energy storage film in energy storage dielectric materials, and using the interlaced co-lattice interface to form an abnormal electronic structure, the problem of insufficient performance of existing materials in high voltage and high frequency pulse capacitor applications is solved, and the effects of high discharge density and long cycle life are achieved.

CN119730719APending Publication Date: 2025-03-28SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924766.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing energy storage dielectric materials to combine high energy storage density, high discharge efficiency and long cycle life, especially in high voltage and high refrigeration pulse capacitor applications.

Method used

Relaxed ferroelectric/antiferroelectric superlattice energy storage film is used to form a uniformly arranged co-cluster interface through the interlaced arrangement between the relaxed ferroelectric phase and the antiferroelectric phase, which promotes the formation of abnormal electronic structures, thereby improving ferroelectric properties and dielectric properties.

Benefits of technology

It significantly improves the discharge density and cycle life of energy storage dielectric materials, enhances ferroelectric and dielectric properties, and is suitable for pulse capacitors with high power density and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730719A_ABST
    Figure CN119730719A_ABST
Patent Text Reader

Abstract

The invention relates to the field of energy storage dielectric materials, in particular to a relaxor ferroelectric / antiferroelectric superlattice energy storage film and a preparation method and application thereof. The superlattice energy storage film comprises a single crystal substrate and a superlattice energy storage film covering the surface of the single crystal substrate, the superlattice energy storage film comprises a plurality of relaxor ferroelectric phases and a plurality of antiferroelectric phases, and the relaxor ferroelectric phases and the antiferroelectric phases are arranged in a staggered mode to form a plurality of coherent interfaces. Through the unique structural design of the superlattice energy storage film and the formation of an abnormal electronic structure, the ferroelectric property and the dielectric property of the film are remarkably improved. Therefore, the thin film can accumulate charges more effectively in the energy storage process, and energy loss is reduced; and the discharge density and the cycle life of the film are also improved, and a new thought and method are provided for the development of an energy storage dielectric material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage dielectric materials, and in particular to a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film and a preparation method and application thereof. Background Art

[0002] The key bottleneck of high-performance integrated pulse energy storage dielectric materials is that technical requirements such as high withstand voltage, high power density and long life are difficult to achieve in the same type of materials. Among the numerous energy storage dielectric materials, linear dielectrics have limited their chip-based and integrated applications due to their small dielectric constant and low energy storage density. Among nonlinear dielectrics, ferroelectric and antiferroelectric materials have higher dielectric constants. In addition, antiferroelectric (A) materials generally have twin structures and high-density head-to-tail relative domains. The existence of these characteristics makes antiferroelectric materials have high electrical strength and high energy storage density. However, in the actual use of cutting-edge pulse technology equipment, the pulse capacitors formed by these antiferroelectric materials need to withstand high voltage and high repetition rate to achieve the state of high power density output of the pulse capacitor; and antiferroelectric materials have double hysteresis loop characteristics and polarization pinning effect under high electric fields, which will lead to high discharge residual voltage and short cycle life in the high-voltage pulse discharge process. Relaxor ferroelectric (R) materials have unique microdomain structures and near-zero residual polarization, which makes R materials have the advantages of fast dielectric response, high discharge efficiency, fast rate, and long cycle life, but R materials have low dielectric strength and low energy storage density. Therefore, it is difficult to form energy storage dielectric materials using R materials and A materials alone to have the characteristics of high energy storage density, high discharge efficiency and long cycle life, which makes the electrical performance of energy storage dielectric materials poor.

[0003] At present, R material and A material can be stacked to form a composite film. Although the composite film is no longer a single phase modification or multi-component composite doping, which provides a new angle for regulating the energy storage characteristics of dielectrics, the energy storage density of the composite film is still at the conventional thin film level, which is difficult to meet the material requirements of integrated pulse capacitors with high discharge density and long cycle life required for the integration of advanced pulse power systems. Summary of the invention

[0004] The present application provides a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film and a preparation method and application thereof to solve the following technical problem: how to improve the discharge density and cycle life of energy storage dielectric materials.

[0005] In the first aspect, the present application provides a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, which is covered on the surface of a single crystal substrate, and the superlattice energy storage film includes multiple relaxor ferroelectric phases and multiple antiferroelectric phases, and the relaxor ferroelectric phases and the antiferroelectric phases are alternately arranged to form multiple coherent interfaces.

[0006] Optionally, the relaxor ferroelectric phase is a lead-free perovskite structure, and the antiferroelectric phase is a perovskite structure.

[0007] Optionally, if the relaxor ferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the relaxor ferroelectric phase;

[0008] If the antiferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the antiferroelectric phase.

[0009] Optionally, the thickness of the relaxor ferroelectric phase is 20 nm to 25 nm, and the thickness of the antiferroelectric phase is 20 nm to 25 nm.

[0010] Optionally, the thickness of the superlattice energy storage film is ≥40nm.

[0011] Optionally, the type of the single crystal substrate includes at least one of the following: Si, LaAlO3 and SrTiO3; and / or

[0012] The relaxor ferroelectric phase includes (Sr, Ca, Bi)TiO3 and / or (Sr, Ca)TiO3; and / or

[0013] The types of the antiferroelectric phase include (Pb, La)(Zr, Ti)O3 and / or AgNbO3.

[0014] In a second aspect, the present application provides a method for preparing the superlattice energy storage film according to the first aspect, the method comprising:

[0015] Obtaining a first ceramic target material of a relaxor ferroelectric phase and a second ceramic target material of an antiferroelectric phase;

[0016] The first ceramic target and the second ceramic target are respectively arranged at positions with a preset distance from the surface of the single crystal substrate;

[0017] The first ceramic target material and the second ceramic target material are used to perform pulsed laser deposition on the surface of the single crystal substrate to obtain a single crystal substrate containing a superlattice energy storage film.

[0018] Optionally, the use of the first ceramic target and the second ceramic target to perform pulsed laser deposition on the surface of the single crystal substrate to obtain the single crystal substrate containing the superlattice energy storage film comprises the steps of:

[0019] Performing a first pulse laser deposition on the surface of the single crystal substrate using the first ceramic target and the second ceramic target under a first preset pulse frequency to obtain a pre-treated surface single crystal substrate;

[0020] The first ceramic target material and the second ceramic target material are used to perform a second pulse laser deposition on the surface of the pretreated surface single crystal substrate under the condition of a second preset pulse frequency to obtain a single crystal substrate containing a superlattice energy storage film.

[0021] Optionally, the preset spacing is 4.5 cm to 5.5 cm;

[0022] The first preset pulse frequency is 1 Hz, and the second preset pulse frequency is 5 Hz;

[0023] The laser wavelengths of the first pulse laser deposition and the second pulse laser deposition are 248 nm, respectively, and the pulse widths of the first pulse laser deposition and the second pulse laser deposition are 25 ns, respectively.

[0024] In a third aspect, the present application provides a pulse capacitor, which includes the superlattice energy storage film described in the first aspect.

[0025] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0026] The embodiments of the present application provide a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film. The superlattice energy storage film can form a uniformly arranged coherent interface between the relaxor ferroelectric phase and the antiferroelectric phase by alternating the relaxor ferroelectric phase and the antiferroelectric phase. The coherent interface is a perovskite superlattice heterointerface, which can form an abnormal electronic structure in the superlattice energy storage film. The abnormal electronic structure will cause the superlattice energy storage film to produce strain effect and interface effect, which will further affect the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0029] Figure 1 A schematic diagram of the product structure of a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in Example 1 of the present application;

[0030] Figure 2A schematic flow chart of a method for preparing a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in an embodiment of the present application;

[0031] Figure 3 A detailed schematic diagram of a method for preparing a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in an embodiment of the present application;

[0032] Figure 4 : is a characteristic curve diagram of the hysteresis loop of the superlattice energy storage film of Example 1, Comparative Example 1 and Comparative Example 2 of the present application, wherein: Figure 4 (a) is a characteristic curve diagram of the hysteresis loop of the superlattice energy storage film provided in Comparative Example 2 of the present application, Figure 4 (b) is a characteristic curve diagram of the hysteresis loop of the superlattice energy storage film provided in Comparative Example 1 of the present application, Figure 4 (c) is a characteristic curve diagram of the hysteresis loop of the superlattice energy storage film provided in Example 1 of the present application.

[0033] Figure 5 A schematic diagram of a product of a superlattice energy storage film provided in Comparative Example 1 of the present application;

[0034] Figure 6 A schematic diagram of a product of a superlattice energy storage film provided in Comparative Example 2 of the present application;

[0035] Figure 7 A product schematic diagram of a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in Examples 1 and 3 of the present application;

[0036] Figure 8 Schematic diagram of the forming principle of a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in Example 1 of the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0038] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited number (fractional or integer) within the indicated range.

[0039] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions, refers to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.

[0041] Figure 1 The schematic diagram of the product structure of a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in Example 1 of the present application is exemplarily shown;

[0042] Figure 8 A schematic diagram of the forming principle of a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in Example 1 of the present application is exemplarily shown;

[0043] like Figure 1 and Figure 8 As shown, an embodiment of the present application provides a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, wherein the superlattice energy storage film is covered on the surface of a single crystal substrate, and the superlattice energy storage film includes multiple relaxor ferroelectric phases and multiple antiferroelectric phases, and the relaxor ferroelectric phases and the antiferroelectric phases are alternately arranged to form multiple coherent interfaces.

[0044] It should be noted that the unit cell period number n of the relaxor ferroelectric phase and the unit cell period number m of the antiferroelectric phase can be adjusted according to actual needs. Specifically, the unit cell period number n of the relaxor ferroelectric phase can be changed by adjusting the formula composition of the first ceramic target material (the degree of adjustment can be set according to the target value parameters of the dielectric and ferroelectric properties of the relaxor superlattice energy storage film), and the unit cell period number m of the antiferroelectric phase can be changed by adjusting the formula composition of the second ceramic target material (the degree of adjustment can be set according to the target value parameters of the dielectric and ferroelectric properties of the relaxor superlattice energy storage film). In addition, the above two adjustments can obtain ceramic targets with different relaxation degrees and antiferroelectric properties.

[0045] In summary, the embodiment of the present application provides a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, which forms a uniformly arranged coherent interface through the staggered arrangement of the relaxor ferroelectric phase and the antiferroelectric phase, and this coherent interface is a perovskite superlattice heterogeneous interface, which can induce the formation of an abnormal electronic structure in the superlattice energy storage film. This abnormal electronic structure not only enhances the strain effect and interface effect of the superlattice energy storage film, but also significantly improves the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material. Specifically: the design of the superlattice energy storage film cleverly combines the characteristics of the relaxor ferroelectric phase and the antiferroelectric phase. The relaxor ferroelectric phase is known for its high polarization intensity and low residual polarization intensity, which is conducive to the accumulation and rapid release of charge in the energy storage process; while the antiferroelectric phase has a stable domain structure and low dielectric loss, which provides good energy storage efficiency and stability for the film. Through the staggered setting of the two, a uniform and dense coherent interface network is formed inside the superlattice energy storage film. These coherent interfaces, as perovskite superlattice heterogeneous interfaces, have a profound impact on the electronic structure of the superlattice energy storage film. They break the periodicity of the original lattice and form an abnormal electronic structure, which makes the transmission and distribution of electrons in the film more complex and diverse. This abnormal electronic structure not only enhances the strain effect of the superlattice energy storage film, so that the superlattice energy storage film can maintain stable electrical properties under external stress; it also significantly enhances the interface effect, making physical phenomena such as charge accumulation and domain reversal at the interface more significant. The enhancement of strain effect and interface effect further affects the ferroelectric and dielectric properties of the superlattice energy storage film. In terms of ferroelectric properties, the polarization intensity and residual polarization intensity of the superlattice energy storage film have been significantly improved, which enables the superlattice energy storage film to accumulate charge more effectively and release it quickly during the energy storage process. In terms of dielectric properties, the dielectric constant and dielectric loss of the superlattice energy storage film have been optimized, making the film respond more quickly and stably under high-frequency electric fields.

[0046] Therefore, the embodiment of the present application provides a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, which significantly improves the ferroelectric and dielectric properties of the film through its unique structural design and the formation of an abnormal electronic structure. This not only enables the film to accumulate charge more effectively and reduce energy loss during the energy storage process; it also improves the discharge density and cycle life of the film, providing new ideas and methods for the development of energy storage dielectric materials.

[0047] In some optional embodiments, the relaxor ferroelectric phase is a lead-free perovskite structure, and the antiferroelectric phase is a perovskite structure.

[0048] In some optional embodiments, if the relaxor ferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the relaxor ferroelectric phase;

[0049] If the antiferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the antiferroelectric phase;

[0050] In these embodiments, it is clarified that the relaxor ferroelectric phase is a lead-free perovskite structure, and the antiferroelectric phase is a perovskite structure. In addition, when the relaxor ferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the relaxor ferroelectric phase, or when the antiferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the antiferroelectric phase. The distribution of the relaxor ferroelectric phase and the antiferroelectric phase can be clarified, so that a large number of uniformly arranged coherent interfaces can be formed. The coherent interface is a perovskite superlattice heterointerface, which can form an abnormal electronic structure in the superlattice energy storage film, and the abnormal electronic structure will cause the superlattice energy storage film to produce strain effect and interface effect, which will further affect the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material.

[0051] In some optional embodiments, the thickness of the relaxor ferroelectric phase is 20 nm to 25 nm, and the thickness of the antiferroelectric phase is 20 nm to 25 nm;

[0052] In these embodiments, the thickness of the relaxor ferroelectric phase can be 20nm~25nm, and the thickness of the antiferroelectric phase can be 20nm~25nm, so that the relaxor ferroelectric phase and the antiferroelectric phase have sufficient thickness. The relaxor ferroelectric phase and the antiferroelectric phase of sufficient thickness can form enough coherent interfaces. A sufficient number of coherent interfaces can form an abnormal electronic structure in the superlattice energy storage film, and the abnormal electronic structure will cause the superlattice energy storage film to produce strain effect and interface effect, which will further affect the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material.

[0053] The thickness of the relaxor ferroelectric phase may be 20 nm, 21 nm, 22 nm, 23 nm, 24 nm or 25 nm.

[0054] The thickness of the antiferroelectric phase may be 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, or 25 nm.

[0055] In some optional embodiments, the thickness of the superlattice energy storage film is ≥40nm;

[0056] In these embodiments, the thickness of the superlattice energy storage film can be ≥40nm, which enables the superlattice energy storage film to have enough relaxed ferroelectric phases and antiferroelectric phases, thereby forming a sufficient amount of abnormal electronic structure. The abnormal electronic structure will cause the superlattice energy storage film to produce strain effect and interface effect, which will further affect the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material.

[0057] The thickness of the superlattice energy storage film may be 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm or 50 nm.

[0058] In some optional embodiments, the type of the single crystal substrate includes at least one of the following: Si, LaAlO3 and SrTiO3; and / or

[0059] The relaxor ferroelectric phase includes (Sr, Ca, Bi)TiO3 and / or (Sr, Ca)TiO3; and / or

[0060] The types of the antiferroelectric phase include (Pb, La)(Zr, Ti)O3 and / or AgNbO3;

[0061] In these embodiments, the type of single crystal matrix may include: at least one of Si, LaAlO3 and SrTiO3, the type of relaxor ferroelectric phase may include (Sr,Ca,Bi)TiO3 and / or (Sr,Ca)TiO3, and the type of antiferroelectric phase may include (Pb,La)(Zr,Ti)O3 and / or AgNbO3, which can cover typical single crystal matrix, relaxor ferroelectric phase and antiferroelectric phase, so as to facilitate the subsequent formation of sufficient abnormal electronic structure, and the abnormal electronic structure will cause strain effect and interface effect in the superlattice energy storage film, which will further affect the ferroelectric and dielectric properties of the superlattice energy storage film, thereby improving the discharge density and cycle life of the energy storage dielectric material.

[0062] Figure 2 The schematic diagram of the process of preparing a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in an embodiment of the present application is exemplarily shown;

[0063] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a method for preparing the superlattice energy storage film, the method comprising:

[0064] S1. Obtaining a first ceramic target of a relaxor ferroelectric phase and a second ceramic target of an antiferroelectric phase;

[0065] S2. The first ceramic target and the second ceramic target are respectively disposed at positions having a preset distance from the surface of the single crystal substrate;

[0066] S3. Use the first ceramic target and the second ceramic target to perform pulsed laser deposition on the surface of the single crystal substrate to obtain a single crystal substrate containing a superlattice energy storage film.

[0067] This method is a method for preparing the above-mentioned superlattice energy storage film. The specific structure and composition of the superlattice energy storage film can refer to the above-mentioned embodiments. Since this method adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0068] It should be noted that the pulsed laser deposition is carried out on a pulsed laser molecular beam epitaxy platform (MBE), and the first ceramic target and the second ceramic target of different compositions are loaded into a multi-target system, and then the target positions and rotation rates of these ceramic targets are adjusted, and the laser output power and pulse frequency of the pulsed laser deposition are changed, and the temperature of the single crystal substrate is adjusted at the same time, so as to deposit the first ceramic target and the second ceramic target onto the substrate of the single crystal substrate. In the above-mentioned pulsed laser deposition process, the order of sputtering and coating of the first ceramic target of relaxor ferroelectric and the second ceramic target of antiferroelectric can be exchanged on the substrate by setting the rotation rate, and the number of laser sputtering is adjustable, and generally the first ceramic target and the second ceramic target are coated with one layer each after one laser sputtering.

[0069] It should be noted that the working principle of the pulsed laser deposition (PLD) is as follows: by focusing a high-energy pulsed laser on the first ceramic target and the second ceramic target, the surface of each ceramic target is melted or vaporized and ablated through the interaction between the laser beam and each ceramic target, so that the surface of each ceramic target expands outward to form a plasma plume, which provides material flux for the growth of the superlattice energy storage film, and then as the plasma plume contacts the substrate surface, the materials of these ceramic targets begin to nucleate and grow, and finally form a uniform superlattice energy storage film.

[0070] Figure 3 A detailed schematic diagram of a method for preparing a "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in an embodiment of the present application;

[0071] In some optional embodiments, such as Figure 3 As shown, the method of using the first ceramic target and the second ceramic target to perform pulsed laser deposition on the surface of the single crystal substrate to obtain a single crystal substrate containing a superlattice energy storage film comprises the steps of:

[0072] S301. Performing a first pulse laser deposition on the surface of the single crystal substrate using the first ceramic target and the second ceramic target under a first preset pulse frequency to obtain a pre-treated surface single crystal substrate;

[0073] S302. Using the first ceramic target and the second ceramic target to perform a second pulse laser deposition on the surface of the pretreated surface single crystal substrate under the condition of a second preset pulse frequency, to obtain a single crystal substrate containing a superlattice energy storage film;

[0074] In these embodiments, the first ceramic target material and the second ceramic target material are laser sputtered onto the surface of the single crystal substrate by a first pulse laser deposition to preliminarily form a certain thickness of relaxor ferroelectric phase and antiferroelectric phase, thereby facilitating the subsequent second pulse laser deposition to form a single crystal substrate containing a superlattice energy storage film.

[0075] In some optional embodiments, the preset spacing is 4.5 cm to 5.5 cm;

[0076] The first preset pulse frequency is 1 Hz, and the second preset pulse frequency is 5 Hz;

[0077] The laser wavelengths of the first pulse laser deposition and the second pulse laser deposition are 248 nm, respectively, and the pulse widths of the first pulse laser deposition and the second pulse laser deposition are 25 ns, respectively;

[0078] In these embodiments, the preset spacing can be 4.5 cm to 5.5 cm, and the first ceramic target material and the second ceramic target material can be fully sputtered onto the surface of the single crystal substrate to form a relaxor ferroelectric phase and an antiferroelectric phase of sufficient thickness, thereby improving the discharge density and cycle life of the energy storage dielectric material; the first preset pulse frequency is 1 Hz, the second preset pulse frequency is 5 Hz, and the laser wavelength of the first pulse laser deposition and the second pulse laser deposition is 248 nm, and the pulse width of the first pulse laser deposition and the second pulse laser deposition is 25 ns, respectively, which enables the first pulse laser deposition and the second pulse laser deposition to be fully carried out to form a relaxor ferroelectric phase and an antiferroelectric phase of sufficient thickness, thereby improving the discharge density and cycle life of the energy storage dielectric material.

[0079] The preset spacing may be 4.5 cm, 4.6 cm, 4.7 cm, 4.8 cm, 4.9 cm, 5.0 cm, 5.1 cm, 5.2 cm, 5.3 cm, 5.4 cm or 5.5 cm.

[0080] Based on a general inventive concept, an embodiment of the present application provides a pulse capacitor, which includes the superlattice energy storage film.

[0081] The pulse capacitor is realized based on the above-mentioned superlattice energy storage film. The specific structure and composition of the superlattice energy storage film can refer to the above-mentioned embodiments. Since the pulse capacitor adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0082] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions or conditions recommended by the manufacturer.

[0083] Example 1

[0084] like Figure 2 As shown, a method for preparing a superlattice energy storage film comprises:

[0085] S1. Obtaining a first ceramic target of a relaxor ferroelectric phase and a second ceramic target of an antiferroelectric phase;

[0086] S2. The first ceramic target and the second ceramic target are respectively disposed at positions having a preset distance from the surface of the single crystal substrate;

[0087] S301. Performing a first pulse laser deposition on the surface of a single crystal substrate using a first ceramic target and a second ceramic target under a first preset pulse frequency to obtain a pretreated surface single crystal substrate;

[0088] S302. Performing a second pulse laser deposition on the surface of the pre-treated surface single crystal substrate using the first ceramic target and the second ceramic target under the condition of a second preset pulse frequency to obtain a single crystal substrate containing a superlattice energy storage film; the specific process is as follows:

[0089] 1. Preparation before deposition:

[0090] According to the target value parameters of the dielectric and ferroelectric properties of the superlattice energy storage film, a suitable first ceramic target material Sr is selected. 0.49 Ca 0.21 Bi 0.2 TiO3 (SCBT) target and second ceramic target Pb 0.9325 La 0.045 Zr 0.02 Ti 0.08 O3(PLZT) target.

[0091] Substrate cleaning: The single crystal substrate was ultrasonically cleaned in acetone and alcohol for 15 min respectively, then rinsed with deionized water, and finally dried to obtain a pure single crystal substrate.

[0092] Installation of the first ceramic target, the second ceramic target and the substrate: The cleaned single crystal substrate and the first ceramic target and the second ceramic target are respectively installed on a rotatable bracket in the high vacuum chamber of the MBE, and the distance between the first ceramic target, the second ceramic target and the single crystal substrate is adjusted to 4.5 cm to 5.5 cm.

[0093] 2. Superlattice energy storage film deposition process:

[0094] The energy of the high-energy pulse laser was set to 200 mJ, the pulse frequency to 5 Hz, and a single crystal Si wafer was used as the substrate.

[0095] (1) Pre-sputtering: In a vacuum environment, turn on the laser so that the first ceramic target and the second ceramic target are rotated with the substrate (10 rot / min), set the pulse frequency of the high-energy pulse laser to 1 Hz, wear protective glasses and adjust the pre-sputtering laser to center the target to form a thin film on the surface of the substrate.

[0096] (2) Formal sputtering: adjust the pulse laser frequency of the high-energy pulse laser to 5 Hz, rotate the target holder to select the first ceramic target for pulse laser deposition, and the pulse laser deposition time is 5 minutes. After the deposition is completed, turn off the high-energy pulse laser, and then rotate the target holder to replace it with the second ceramic target. Continue pulse laser deposition for 5 minutes to eventually form a staggered layer of relaxor ferroelectric phase and a layer of antiferroelectric phase. The thickness of the obtained relaxor ferroelectric phase is 20nm~25nm, and the thickness of the antiferroelectric phase is 20nm~25nm. Finally, the total thickness of the superlattice energy storage film is 45nm~50nm.

[0097] 3. Operation after film deposition is completed:

[0098] After the second pulse laser deposition is completed, turn off the high-energy pulse laser, keep the cavity pressure unchanged, close the electromagnetic valve, and at the same time close the hand-operated valve in front of the equipment, quickly introduce argon gas, and then replace the sample through the sample transfer rod and the injection chamber.

[0099] Example 2

[0100] Based on the contents disclosed in Example 1, the following modifications are further made:

[0101] During the actual sputtering process, the second ceramic target is used first and then the first ceramic target.

[0102] Example 3

[0103] Based on the contents disclosed in Example 1, the following modifications are further made:

[0104] LaAlO3 is used as the substrate.

[0105] Example 4

[0106] Based on the contents disclosed in Example 1, the following modifications are further made:

[0107] (2) Formal sputtering: adjust the pulse laser frequency of the high-energy pulse laser to 5 Hz, rotate the target holder to select the first ceramic target for pulse laser deposition, and the pulse laser deposition time is 5 minutes. After the deposition is completed, turn off the high-energy pulse laser, rotate the target holder to replace it with the second ceramic target, and continue the pulse laser deposition for 5 minutes. After the deposition is completed, turn off the high-energy pulse laser, rotate the target holder to replace it with the first ceramic target, and continue the pulse laser deposition for 5 minutes. Finally, a three-layer staggered structure of a layer of relaxor ferroelectric phase, a layer of antiferroelectric phase and a layer of relaxor ferroelectric phase is formed. The thickness of the obtained relaxor ferroelectric phase is 20nm~23nm, and the thickness of the antiferroelectric phase is 20nm~23nm. Finally, the total thickness of the superlattice energy storage film is 60nm~69nm.

[0108] Example 5

[0109] Based on the contents disclosed in Example 4, the following modifications are further made:

[0110] During the formal sputtering process, the second ceramic target, the first ceramic target and the second ceramic target are used in sequence, and finally the total thickness of the superlattice energy storage film is 60nm to 69nm.

[0111] Comparative Example 1

[0112] Based on the contents disclosed in Example 1, the following modifications are further made:

[0113] The second ceramic target is not used, and only the first ceramic target is used.

[0114] Comparative Example 2

[0115] Based on the contents disclosed in Example 1, the following modifications are further made:

[0116] The first ceramic target is not used, and only the second ceramic target is used.

[0117] Related experiments and effect data:

[0118] 1. Collect the superlattice energy storage films obtained in Example 1, Example 3 and each comparative example respectively, wherein the superlattice energy storage film of Comparative Example 1 is as follows Figure 5 As shown, the superlattice energy storage film of Comparative Example 2 is as shown Figure 6 In addition, the samples of Example 1 and Example 3 were statistically analyzed, and the results are as follows Figure 7 shown.

[0119] Then, the hysteresis loop characteristics of the superlattice energy storage film obtained in Example 1 and each comparative example are statistically analyzed. The results are as follows: Figure 4 As shown, the results show that the "relaxor ferroelectric / antiferroelectric" superlattice energy storage film provided in the embodiment of the present application combines the respective advantages of the relaxor ferroelectric phase and the antiferroelectric phase, and through the synergistic effect of the superlattice and the regulation of the sequence structure, it can achieve the application goal of pulse capacitors with higher energy storage density.

[0120] 2. Statistics of electrical properties of superlattice energy storage films obtained in various embodiments and comparative examples

[0121] Capacitors were prepared from the single crystal substrate of the superlattice energy storage film obtained in each embodiment and comparative example, and corresponding charge and discharge cycle life tests lasting 6 hours and 10 hours were carried out to measure the cycle life data and the current density converted under the electric field of 37.5 V / μm. The results are shown in Table 1.

[0122] Table 1 Charge and discharge cycle life test data and current density results of various embodiments and comparative examples

[0123]

[0124] It can be seen from Table 1 that the superlattice energy storage film provided by each embodiment has a good cycle life and a high current density.

[0125] In summary, the "relaxed ferroelectric / antiferroelectric" superlattice energy storage film provided in the embodiment of the present application significantly improves the ferroelectric and dielectric properties of the film through its unique structural design and the formation of an abnormal electronic structure. This not only enables the film to accumulate charge more effectively and reduce energy loss during the energy storage process; it also improves the discharge density and cycle life of the film, providing new ideas and methods for the development of energy storage dielectric materials.

[0126] In addition, an embodiment of the present application provides a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, which can adjust the composition of the relaxor ferroelectric phase and the antiferroelectric phase to obtain superlattice epitaxial sources with different degrees of relaxation and antiferroelectricity. The superlattice energy storage film can be epitaxially grown on substrates of different single crystal substrates, thereby constructing a superlattice energy storage film with both relaxor ferroelectric and antiferroelectric properties.

[0127] In addition, an embodiment of the present application provides a method for preparing a "relaxed ferroelectric / antiferroelectric" superlattice energy storage film. The method is based on a pulsed laser molecular beam epitaxy platform. By switching different target material rotating racks, the order of the relaxor ferroelectric phase and the antiferroelectric phase is achieved. In addition, by controlling the frequency and power of the pulsed laser, the number of lattice periods of the relaxor ferroelectric phase and the antiferroelectric phase in each layer can be controlled, thereby obtaining a superlattice energy storage film with different relaxor ferroelectric phase and antiferroelectric phase sequence structures to optimize and improve the composite electrical properties of the superlattice.

[0128] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.

Claims

1. A "relaxed ferroelectric / antiferroelectric" superlattice energy storage film, which covers the surface of a single crystal substrate, and includes multiple relaxor ferroelectric phases and multiple antiferroelectric phases, wherein the relaxor ferroelectric phases and the antiferroelectric phases are alternately arranged to form multiple coherent interfaces.

2. According to the superlattice energy storage film of claim 1, the relaxor ferroelectric phase is a lead-free perovskite structure, and the antiferroelectric phase is a perovskite structure.

3. The superlattice energy storage film according to claim 1, wherein if the relaxor ferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the relaxor ferroelectric phase; If the antiferroelectric phase is the first layer covering the surface of the single crystal substrate, the outermost layer of the superlattice energy storage film is the antiferroelectric phase. 4 . The superlattice energy storage film according to claim 1 , wherein the relaxor ferroelectric phase has a thickness of 20 nm to 25 nm, and the antiferroelectric phase has a thickness of 20 nm to 25 nm. The superlattice energy storage film according to claim 4 , wherein the thickness of the superlattice energy storage film is ≥40 nm.

6. The superlattice energy storage film according to claim 1, wherein the type of the single crystal substrate comprises at least one of the following: Si, LaAlO3 and SrTiO3; and / or The relaxor ferroelectric phase includes (Sr, Ca, Bi)TiO3 and / or (Sr, Ca)TiO3; and / or The types of the antiferroelectric phase include (Pb, La)(Zr, Ti)O3 and / or AgNbO3.

7. A method for preparing the superlattice energy storage film according to any one of claims 1 to 6, the method comprising: Obtaining a first ceramic target material of a relaxor ferroelectric phase and a second ceramic target material of an antiferroelectric phase; The first ceramic target and the second ceramic target are respectively arranged at positions with a preset distance from the surface of the single crystal substrate; The first ceramic target material and the second ceramic target material are used to perform pulsed laser deposition on the surface of the single crystal substrate to obtain a single crystal substrate containing a superlattice energy storage film.

8. The method according to claim 7, wherein the first ceramic target and the second ceramic target are used to perform pulsed laser deposition on the surface of the single crystal substrate to obtain a single crystal substrate containing a superlattice energy storage film, comprising the steps of: Performing a first pulse laser deposition on the surface of the single crystal substrate using the first ceramic target and the second ceramic target under a first preset pulse frequency to obtain a pre-treated surface single crystal substrate; The first ceramic target material and the second ceramic target material are used to perform a second pulse laser deposition on the surface of the pretreated surface single crystal substrate under the condition of a second preset pulse frequency to obtain a single crystal substrate containing a superlattice energy storage film.

9. The method according to claim 8, wherein the preset spacing is 4.5 cm to 5.5 cm; The first preset pulse frequency is 1 Hz, and the second preset pulse frequency is 5 Hz; The laser wavelengths of the first pulse laser deposition and the second pulse laser deposition are 248 nm, respectively, and the pulse widths of the first pulse laser deposition and the second pulse laser deposition are 25 ns, respectively.

10. A pulse capacitor, comprising the superlattice energy storage film according to any one of claims 1 to 6.